Characterization of cerebellar electrocortical dynamics under ether anesthesia in rats: a preliminary study using linear spectral and non-linear fractal analyses - Podgorac Kojadinović, Jelena; Petković, Branka; Kalauzi, Aleksandar; Martać, Ljiljana; Sekulić, Slobodan; Stojadinović, Gordana (Archives of Biological Sciences, 2025)
Paper description: Ether, as a general anesthetic, influences the activity of cortical and subcortical regions. Cerebellar electrocortical activity of rats after ether anesthesia was recorded telemetrically with a 16-channel microelectrode system and evaluated by linear and non-linear signal analysis. A transitional period between different depths of anesthesia was evident between the 17th and 19th minute post-induction, suggesting progressive neural reorganization associated with the emergence from the anesthetized state. Monitoring anesthetic depth using linear and non-linear signal analysis could assess patterns of electrocortical activity in the cerebellum and other brain regions. Abstract: The temporal evolution of cerebellar electrocortical activity during emergence from ether anesthesia was investigated using both linear and non-linear analytical methods. Adult male rats underwent operative craniotomy and implantation of a 16-channel microelectrode array targeting the paravermal cerebellar cortex. Following a 7-day recovery period, animals were exposed to ether via inhalation, and cerebellar electrocortical signals were recorded using a wireless acquisition system. Data were quantified through relative spectral power (RSP) across defined frequency bands, Higuchi’s fractal dimension (HFD), and the Hurst exponent (H). A transitional phase between anesthetic depths was identified between the 17th and 19th min post-exposure. This period was characterized by a significant increase in RSP within low-frequency bands and a corresponding decrease in high-frequency bands beginning at the 17th min. Additionally, a marked decrease in HFD and an increase in H were observed at the 19th min, followed by a moderate rebound in HFD and a reduction in H. These findings suggest that non-linear dynamic measures, particularly HFD and H, may offer greater temporal precision in identifying the onset of awakening compared to conventional spectral analysis, highlighting their potential utility in monitoring anesthetic depth.